CONTRIBUCIONN AL CONOCIMIENTO DE LA CITOFISIOLOGIA DE LOS PRECESOS IMMUNLTARIOS Y ALERGICOS I DATOS MORFOLOGICOS - GONZALEZ GUZMAN, IGNACIO (Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, CD MEXICO, DF, MEX, 1949)
Tissues in exptl immunity, especially the human nasal polyp, provide morph data concerning antibody formation Neutrophils and eosinophils with band forms or 2 nuclear lobes contain 2-3 silver-staining granules sometimes surrounded by a fine cortex of
BOL MEN BAN REF JAL
Keywords: CONTRIBUCION, CONOCIMIENTO, CITOFISIOLOGIA, PRECESOS IMMUNLTARIOS, ALERGICOS, DATOS MORFOLOGICOS; CIENCIAS DE LA VIDA; BIOLOGIA CELULAR; CULTIVO CELULAR